Analisis Pengaruh Media Sosial terhadap Penyebaran Pesan Dakwah - Shilvia Maharani; Ina Sitiyani; Adhi Kusuma (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of digital technology has brought significant changes in the way of communication and dissemination of information, including in Islamic preaching activities. Social media such as Instagram, YouTube, TikTok, Facebook, and Twitter are now strategic means for preachers to convey Islamic messages more widely, quickly, and effectively. This study aims to analyze the role of social media in the process of disseminating preaching messages in the digital era, with a descriptive qualitative approach. The results of the study show that social media not only acts as a means of conveying messages, but also as an interactive space that allows for two-way communication between preachers and audiences. Through various forms of content such as short videos, infographics, podcasts, and live streaming, preaching becomes more flexible and easily accepted, especially by the younger generation who are familiar with the digital world. In addition, social media also plays a role in shaping the identity of digital preachers who can increase their credibility and influence as religious figures.